Characterization of inflammatory changes in the breast cancer associated adipose tissue and comparison to the unaffected contralateral breast. (December 2021) - Blaszczak, Alecia M.; Quiroga, Dionisia; Jalilvand, Anahita; Torres Matias, Gina S.; Wright, Valerie P.; Liu, Joey; Yu, Lianbo; Bradley, David; Hsueh, Willa A.; Carson, William E.
Abstract: Background: Adipose tissue has emerged as an important window into cancer pathophysiology, revealing potential targets for novel therapeutic interventions. The goal of this study was to compare the breast adipose tissue (BrAT) immune milieu surrounding breast carcinoma and contralateral unaffected breast tissue obtained from the same patient. Materials and methods: Patients undergoing bilateral mastectomy for unilateral breast cancer were enrolled for bilateral BrAT collection at the time of operation. After BrAT was processed, adipocyte and stromal vascular fraction (SVF) gene expression was quantified by PCR. SVF cells were also processed for flow cytometric immune cell characterization. Results: Twelve patients underwent bilateral mastectomy for unilateral ductal carcinoma. BrAT adipocyte CXCL2 gene expression trended higher in the tumor-affected breast as compared to the unaffected breast. Macrophage MCP-1 and PPARγ gene expression also tended to be higher in the tumor-affected breasts. T cell gene expression of FOXP3 (p = 0.0370) were significantly greater in tumor-affected breasts than unaffected breasts. Affected BrAT contained higher numbers of Th2 CD4 + cells (p = 0.0165) and eosinophils (p = 0.0095) while trending towards increased macrophage and lower Th1 CD4 + cells infiltration than tumor-affected BrAT. Conclusion: This preliminary study aimed to identify the immunologic environment present within BrAT and is the first to directly compare this in individual patients' tumor-associated and unaffected BrAT. These findings suggest that cancer-affected BrAT had increased levels of T cell specific FOXP3 and higher levels of anti-inflammatory/regulatory cells compared to the contralateral BrAT. HIGHLIGHTS: - In the obese state, adipose tissue can be a major driver of inflammation and contributes to the development of cancer. - In this study, breast adipose tissue from twelve patients who had bilateral mastectomies for unilateral breast cancer was compared across tumor-affected and tumor-unaffected breasts. - Tumor-affected breast adipose was found to have increased T regulatory cell gene expression and increased anti-inflammatory/regulatory immune cells present compared to tumor-unaffected breast adipose.